Pingyangmycin Activates Oral Carcinoma Cell Autophagy via the Phosphorylation of the PI3K/AKT/mTOR Axis to Achieve the Purpose of Treating Oral Carcinoma - Wei Xu; Laijian Zhang; Zhi Chen; Hao Wang; Zhongyi Yan (Emergency Medicine International)
Objective. The aim of the study is to investigate the role of pingyangmycin (PYM) in oral carcinoma (OC) cell autophagy via the PI3K/AKT/mTOR axis. Methods. 200 μL PYM culture solution with a concentration of 100 μg/ml (low PYM (L-PYM) group), 300 μg/ml (middle PYM (M-PYM) group), 500 μg/ml (high PYM (H-PYM) group), and the same amount of conventional medium (normal control (NC)) were added to the purchased OC cell line SCC-25, respectively, and the PI3K/AKT/mTOR pathway expression, autophagy protein levels, cell activity, and apoptosis rate were determined. Subsequently, we selected OC cells co-cultured with PYM with the concentration of the most significant intervention effect and 740Y-P, a specific activator of the PI3K/AKT/mTOR axis, and those treated with 740Y-P alone for the aforementioned detection. Results. L-PYM, M-PYM, and H-PYM groups all showed decreased PI3K, AKT, mTOR, and phosphorylated protein levels (P<0.05). Beclin1 and LC3-II protein levels and apoptosis rate of PYM-intervened OC cells increased, but the activity decreased (P<0.05). Under 740Y-P intervention, the PI3K/AKT/mTOR pathway was activated, cell activity was increased, and the apoptosis rate and autophagy were decreased (P<0.05). Simultaneous use of PYM and 740Y-P led to no difference in cell condition compared with NC (P>0.05P>0.05). Conclusion. PYM can activate OC cell autophagy by inhibiting the phosphorylation of the PI3K/AKT/mTOR axis, and thus, achieving the goal of killing tumor cells.